DOP51 Mucosa-associated microbial signatures associate with objective response prior to the start of anti-TNFα but not vedolizumab or ustekinumab in Crohn's disease patients. (30th January 2023) - Hageman, I; Joustra, V; Zafeiropoulou, K; Davids, M; Hakvoort, T; Probert, F; Satsangi, J; D'Haens, G; De Jonge, W
Abstract: Background: Crohn's disease (CD) is a complex immune-mediated disease of the gastrointestinal tract where the gut microbiome plays an important role. Current biological treatment options in CD include the anti-TNFα agents adalimumab (ADA) and infliximab (IFX), vedolizumab (VDZ), and ustekinumab (USTE). Finding biomarkers to predict therapy response is still a clinical unmet need, as the majority of CD patients fail to reach endoscopic remission within 1 year of treatment. While the majority of studies focus on fecal samples, mucosa-adherent bacterial signature could bring forth stable biomarkers. In this study, we sought to identify signatures of the adherent microbiome in intestinal biopsies aimed at differentiating responders (R) from non-responders (NR), prior to the start of biological treatment. Methods: We prospectively collected paired ileal and colonic biopsies (stored snapfrozen in -80 ºC) from adult CD patients scheduled to start anti-TNFα (IFX and ADA), VDZ and USTE treatment during baseline endoscopies. After 6-12 months of follow-up, patients were classified as either R or NR based on endoscopic response (≥50% reduction in SES-CD score) in combination with steroid-free clinical response (≥3 point drop in HBI or HBI ≤4) and/or biochemical response (≥50% reduction in C-reactive protein (CRP) and fecal calprotectin or a basal CRP ≤5 g/mL and fecal calprotectin ≤250 µg/g). Microbiome composition of the biopsies was determined using 16S RNA gene V3V4 amplicon sequencing. Results: For the anti-TNFα cohort, we included in total 36 CD patients (21R and 18 NR), for VDZ cohort a total of 44 patients (28 R and 16 NR) and for USTE cohort a total of 40 patients (20R and 20 NR).When comparing α-diversity and β-diversity between R and NR, we did not find significant differences in ileal and colonic samples at baseline for the VDZ and USTE cohorts. Notable, for the anti-TNFα cohort (table 1), we obtained significant differences when comparing α-diversity (p=0.028) and β-diversity between R and NR. We demonstrated differences between colonic R and NR in taxa abundance for ASVs associated with the phyla Bacteroidetes, Firmicutes, Fusobacteria, Proteobacteria (figure 1). Furthermore, ASVs associated with Firmicutes, Bacteroidetes, Actinobacteria are different in abundance between ileal R and NR (figure 2). Figure 1: Differential taxa abundance colonic R vs NR anti-TNFα Figure 2: Differential taxa abundance ileal R vs NR anti-TNFα Figure 3: graphical summary Conclusion: Here, we investigated the microbial signature of R and NR before the start of treatment of three separate cohorts and we demonstrated that the mucosa-associated microbiome differentiates R and NR to anti-TNFα therapy. Further analyses as part of the EPIC Pioneer study, are ongoing.